2018
DOI: 10.1111/coa.13234
|View full text |Cite
|
Sign up to set email alerts
|

Septoplasty versus non‐surgical management for nasal obstruction due to a deviated nasal septum in adults: A modelling study of cost‐effectiveness

Abstract: Objective The objective of this study was to demonstrate how decision‐analytic modelling can help to determine circumstances under which surgery may become cost‐effective, using septoplasty as an example. Design We developed a decision‐analytic model comparing septoplasty to non‐surgical management for nasal obstruction in adults with a deviated septum. Based on the estimated cost difference between both treatments, we calculated the minimal (a) gain in quality‐adjusted life‐years, or (b) reduction in producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Given the relatively small differences in the natural distribution of septal deviations between men and women, it is surprising that several recent studies analysing predictors and outcome in septoplasty report a considerable male predominance in the septoplasty cohorts (4). Data from the Swedish National Septoplasty Register (SNSR) show that around 70% of the patients are males, which is in line with other studies (1,4,6,7). It has been proposed that men are more involved in nasal traumas related to sports activities, assaults and motor vehicle accidents and therefore experience more problems with their nasal breathing due to a nasal obstruction (8).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Given the relatively small differences in the natural distribution of septal deviations between men and women, it is surprising that several recent studies analysing predictors and outcome in septoplasty report a considerable male predominance in the septoplasty cohorts (4). Data from the Swedish National Septoplasty Register (SNSR) show that around 70% of the patients are males, which is in line with other studies (1,4,6,7). It has been proposed that men are more involved in nasal traumas related to sports activities, assaults and motor vehicle accidents and therefore experience more problems with their nasal breathing due to a nasal obstruction (8).…”
Section: Introductionsupporting
confidence: 89%
“…There were no objective data of nasal air-flow resistance or intranasal geometry, such as rhinomanometry or acoustic rhinometry available in this study. PROMS and objective measures, however, often show conflicting results ( 1 , 4 ). It is thus important to consider both PROMS and objective measures in the follow up of septoplasty surgery as partly different but complementary outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled trials or non-randomized comparative studies on the (cost-) effectiveness of septoplasty have not been published before [5]. Previous modeling research based on publicly available data sources demonstrated that septoplasty incurs significant additional costs compared to non-surgical management, especially considering the productivity losses due to postoperative recovery [10]. However, as effectiveness data were lacking, the relation between costs and effects of septal surgery remained unclear.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Both health-related quality of life and objective measurements of nasal airflow were found to improve after septoplasty. Nonetheless, previous modeling research demonstrated that septal surgery incurs significant additional costs compared to non-surgical management [10]. Considering the rising demand for care and growing strain on resources, it is important to weigh the benefits of an intervention against its costs, in order to justify its use to society [11].…”
Section: Introductionmentioning
confidence: 99%